Impact of the Trans Pacific Partnership to Indonesia - Syadullah, Makmun (International Journal of Economics and Financial Issues, 2016)
The paper is structured aims to analyze the extent to which profits and losses if Indonesia joined the Trans-Pacific Partnership. Based on the analysis it can be concluded that in general the TPP will have a negative impact on Indonesia, both in terms of trade in goods and services, investment, intellectual property rights and state. Considering the negative impacts of TPP and taking into account the 12 countries that joined the TPP, the four countries are of ASEAN which has had cooperation through AFTA, and there have been bilateral cooperation with Peru, the Government should in the short-term more emphasis on bilateral cooperation, particularly with the United States. Keywords: trade, economic integration, international investment. JEL Classifications: F13, F15, F21